'Vitamin D and cognition in older adults': updated international recommendations. (19th July 2014) - Annweiler, C.; Dursun, E.; Féron, F.; Gezen‐Ak, D.; Kalueff, A. V.; Littlejohns, T.; Llewellyn, D. J.; Millet, P.; Scott, T.; Tucker, K. L.; Yilmazer, S.; Beauchet, O.
Abstract Background Hypovitaminosis D, a condition that is highly prevalent in older adults aged 65 years and above, is associated with brain changes and dementia. Given the rapidly accumulating and complex contribution of the literature in the field of vitamin D and cognition, clear guidance is needed for researchers and clinicians. Methods International experts met at an invitational summit on 'Vitamin D and Cognition in Older Adults'. Based on previous reports and expert opinion, the task force focused on key questions relating to the role of vitamin D in Alzheimer's disease and related disorders. Each question was discussed and voted using a Delphi‐like approach. Results The experts reached an agreement that hypovitaminosis D increases the risk of cognitive decline and dementia in older adults and may alter the clinical presentation as a consequence of related comorbidities; however, at present, vitamin D level should not be used as a diagnostic or prognostic biomarker of Alzheimer's disease due to lack of specificity and insufficient evidence. This population should be screened for hypovitaminosis D because of its high prevalence and should receive supplementation, if necessary; but this advice was not specific to cognition. During the debate, the possibility of 'critical periods' during which vitamin D may have its greatest impact on the brain was addressed; whether hypovitaminosis D influences cognition actively through deleterious effects and/or passively by loss of neuroprotection was also considered. Conclusions The international task force agreed on five overarching principles related to vitamin D and cognition in older adults. Several areas of uncertainty remain, and it will be necessary to revise the proposed recommendations as new findings become available.